EFEKTIVITAS PENGGUNAAN VIDEO DENGAN MODEL FLIPPED CLASROOM TENTANG HUKUM NEWTON UNTUK MENINGKATKAN HASIL BELAJAR - Veronika Dea Agustine; Haratua Tiur Maria S; Muhammad Musa Syarif Hidayatullah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The effectiveness of utilizing learning videos with the flipped classroom model in improving understudy learning results on Newton's law material in class VIII SMP Negeri 2 Pontianak. The form of the research utilized is a trial with a pretest-posttest design utilizing a paired sample T-test and an independent sample T-test. The example in this study was class VIII A as an exploratory class utilizing learning videos with a flipped classroom model and VIII C as a conventional learning control class. The test in this study was in the form of 20 multiple choice questions. Based on the reference results of data analysis, it is finished zup (1) There is an expansion in understudy learning results later using learning videos by 62.35 with 41% completeness percentage, and conventional learning by 51.79 with 28% completeness percentage. (2) There are differences in the learning outcomes of students in the experimental class and the control class after being given the application of the flipped classroom learning model and conventional learning F = 2,434 with a sig level (0.00 < 0.05). (3) The utilization of learning videos using the flipped classroom model is effective in further developing understudy learning results on Newton's regulation material.